Synthesis and Antibacterial Activities of Mixed Ligands Complexes of Cu(II) and Zn(II) Containing Tridentate Azo Anils Ligands and Bidentate Oxalate Ion - Ameen, Muhammad; Rubina Gilini, Syeda; Naseer, Amina; Shoukat, Ishrat; Danish Ali, Syed; Sadiqa, Ayesha (Asian Journal of Chemistry, 2015)
Mixed ligands complexes of copper(II) and zinc(II) were synthesized using azo anils ((HNPDBAB = 2-(2-hydroxy-5-[(4-nitrophenyl)diazenyl]benzylideneamino)benzoic acid, HPIMNDP = 2-[(2-hydroxyphen yl)imino]methyl-4-[(4-nitrophenyl)diazenyl] phenol) and oxalate ion as a coordinating ligands. Elemental analysis, atomic absorption spectroscopy, FTIR, NMR, UV-visible. were used for the characterizations of synthesized azo anils ligands and their mixed ligands complexes. Distorted octahedral geometry was tentatively proposed for these new mixed ligands M(II) Cu(II) and Zn(II) complexes. Gram-positive (Bacillus subtilis and Staphylococcus aureus) and Gram-negative (Enterobacter aerogenes and Escherichia coli) were screen out for antibacterial activities of azo anils ligands, oxalic acid, metal salts and their mixed ligands M(II) complexes. The antibacterial activities were performed to assess the extent of inhibition potential of free ligand and their mixed ligands M(II) complexes. The results revealed that antibacterial activities of azo anils became more pronounced when these were coordinated to central metal atom.